Modification of the Asthenic State Assessment Scale - SAVCHENKO, Olena; DVORIAKOVSKA, Tata (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Background. Against the backdrop of chronic stress, manifestations of asthenic syndrome are becoming more widespread among Ukrainians. The issue of developing reliable means of psychological assessment of this condition has become acute.Methods. The article presents the results of the Ukrainian-language modification of the Asthenic State Scale (ASS-15) questionnaire. The main psychometric characteristics are determined.Results. Empirical research has shown that some of the questions in the unadapted Ukrainian-language version of the scale demonstrate low reliability and validity, which calls into question its accuracy and diagnostic value. Based on the results of factor analysis, additional subscales were identified that reflect various aspects/domains of asthenic syndrome. Based on the data obtained, the structure of the questionnaire was optimised: questions that showed low reliability and validity were removed. The results of confirmatory factor analysis showed the relevance of implementing a three-component model (X2 = 110, p = 0.05; CFI = 0.961; TLI = 0.953; RMSEA = 0.047, [0.02-0.07]). The updated version of the methodology is more compact, has sufficiently high internal consistency indicators (Cronbach's alpha from 0.70 to 0.83), allows for a differentiated assessment of individual components of asthenic state, and can be recommended for use in clinical, psychological, and scientific research. Conclusions. The article provides justification for the reduction and modification of the Asthenic State Scale and describes the procedure for distinguishing three subscales: cognitive, emotional, and physiological manifestations of asthenia.
Keywords: asthenia; chronic fatigue syndrome; asthenic syndrome; Asthenic State Scale; cognitive manifestations; emotional manifestations; physiological manifestations; psychometric characteristics